Efeito do envelhecimento em diferentes soluções sobre a resistência de união em reparos com resina composta Bulk Fill. - Rosa, Saulo Vinicius da (2017)
Bulk fill resins can be used as dentin replacements, requiring coating by another composite resin, such as a nano-hybrid resin, or they can be used without the need for a new composite resin for their protection. The objective of this work was to evaluate the bond strength of repairs made between different composite resins, after aging in different solutions. Five composite resins were used, one conventional and four bulk fill composites. 2x2x5 mm CP were made in silicone mold and aged for 30 days, after which the resins were given the surface treatment and soon after the repair, becoming a CP with 2x2x10mm. All the resins were combined. The mean values obtained for each test specimen were submitted to the Shapiro Kruskall Wallis test, followed by the Dunn test, p <0.05. The results showed that, after aging in distilled water, Aura bulk fill as base showed statistical differences when compared to the composite resins Z350 (1.27 + 0.95) and Tetric Ceram bulk fill (3.72 + 1.74), the composite resin Tetric Ceram bulk fill used as a base showed that there was statistical difference when Filtek bulk fill composite resin 4,81 (+1,20) was used and when Z350 resin (2.22 + 0.63) and Tetric Ceram bulk fill (2.54 + 0.52). After aging in water / ethanol solution, no statistically significant differences were found between all possible combinations. After aging in nitric acid solution, when Aura bulk fill was used as base there were statistical differences between the repair with Tetric Ceram bulk fill (4.02 + 0.82) and Z350 (1.71 + 1.09 ), when Filtek bulk fill used as base there were statistical differences between Z350 (2.30 + 0.62) and Filtek bulk fill 4.02 (+1.85) used for the repair, with Tetric ceram bulk fill as base there were statistical differences when compared to the composite resin Filtek bulk fill 4,04 (+1,07) and Z350 (1,99 + 0,76). According to the results obtained it was possible to verify that, in the majority of the comparisons made among the composite resins evaluated in this study, the composite resins bulk fill obtained better values of bond strength when the composite resins themselves were united bulk fill and the worst values when they received the repair with the composite resin when immersed in acidic solutions and distilled water, it was not possible to observe statistically significant differences when immersing in water / ethane.